Understanding Military Retirement and Supporting Military Retirees in Your Service Network - Kristen Jowers; Martie Gillen (EDIS)
This publication discusses aspects of military retirement, including retirement systems, planning processes, pay and taxes, survivor benefits, and planning resources. Written by Kristen Jowers and Martie Gillen, and published by the UF/IFAS Department of Family, Youth and Community Sciences, October 2023.